220 Nephrostomy for acute obstructive renal failure in women with cervical cancer – is it worth?. (18th September 2019) - Vale, D; Marangoni, M; Silva, ML; Torres, JC; Cassin, W; Machado, H; Bragança, JF
Abstract : Objectives: To evaluate outcomes related to nephrostomy in women before and after cervical cancer treatment for acute obstructive renal failure. Methods: Were included 52 cases of women with cervical cancer IIIB+ and acute obstructive renal failure that have undergone nephrostomy at the University Women's Hospital of Unicamp (Campinas, Brazil), from 2003 to 2017. Two groups were evaluated: before and after radiotherapy treatment (BR and AR). Variables were analyzed by frequencies and survival by Kaplan-Meier curves and log-rank. Results: The mean age was 47.8 years old (ST 13.4), and the mean urea and creatinine before the procedure were respectively 134.8 and 13.2 (ST 76.9 and 29.7). Average days of hospitalization were 25 days. After three years of the procedure, 56% of the women in BR and 100% of the women in AR were dead (p=0.047). The six-months overall survival after nephrostomy was 46.4 in BR and 14.8 in AR, while the one-year overall survival was 19.3 in BR and 3.7 in AR (log-rank three-year overall survival P=0.007). Conclusions: Nephrostomy for acute renal failure due to cervical cancer is associated with prolonged hospitalization regardless of the stage of the treatment. Overall survival was low in both groups, but higher in women in the BT procedure. Although nephrostomy might be considered useful in treatment-naive patients with obstructive renal failure, the validity of this type of treatment in the group of women that had already undergone treatment is not yet defined.